(untitled) (The Voz a Vos Bulletin, 2023)
In 2023 - I Interdisciplinary Theater, Fiesta, and Carnival Assembly course, two EAPEATs were held, one at the Barranquilla Carnival and the other at the Black and White Carnival in Pasto, Nariño. Within the creation laboratory, each member chose a character, disguised or a dance from the different carnivals, and created litanies in relation to their characters, having as reference the Litany Festival of Barranquilla.